PENGARUH KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI TOKO ROTI BROWNIES CINTA CABANG KLATEN - Fitria Nur Septiani; Pemilia Sulistyowati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to indentify and analyze the direct influence of product quality on customer satisfaction among customer of Brownies Cinta Klaten, to identify and analyze the direct influence of price on customer satisfaction among customers of Brownies Cinta Klaten, to indentify and analyze the direct influence of service quality on customers of Brownies Cinta Klaten, and to determine and analyze the simultaneous influence of product quality, price, and service quality on customer satisfaction at the Brownies Cinta Klaten Branch. This research employs a quantitative method with a total sample of 80 respondents who are customers of the Brownies Cinta Klaten Branch. The data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics. The results of the study indicate that product quality has a significant direct effect on customer satisfaction among customers of the Brownies Cinta Klaten Branch. Price also has a significant direct effect on customer satisfaction among these customers. Likewise, service quality has a significant direct effect on customer satisfaction among customers of the Brownies Cinta Klaten Branch. Furthermore, product quality, price and service quality simultaneously have a significant influence on customer satisfaction at the Brownies Cinta Klaten Branch.